The Role of Muhammadiyah in Promoting Islam as Rahmatan Lil ‘Alamin to Counter Religious Radicalism Among University Students - Armansyah, Awang Dhany; Aziz, Akbar Nur; Tago, Mahli Zainuddin (Jurnal Studi Agama dan Masyarakat, 2024)
The spread of religious radicalism is no longer confined to the general public but has also penetrated academic settings, particularly Islamic-based universities, such as Universitas Muhammadiyah Yogyakarta (UMY). This study aims to analyze the role of Muhammadiyah, with its teaching of rahmatan lil ‘alamin, in addressing cases of religious radicalism among students. The research employs a qualitative method with a field study approach and an experimental model. The subjects of the study were 156 undergraduate students from Agribusiness and Islamic Religious Education programs at UMY, class of 2024. Data was collected through pretests and posttests conducted in February 2024. Data analysis involved data collection, reduction, and conclusion drawing. The findings indicate that the implementation of Islam as rahmatan lil ‘alamin in preventing religious radicalism among Agribusiness undergraduates at the Faculty of Agriculture, UMY, was initially 33.7%. After receiving materials delivered by Muhammadiyah as part of its strategy to prevent religious radicalism in higher education, students' understanding of religious radicalism increased to 94%. As a moderate Islamic organization, Muhammadiyah has exemplified the values of Islam as rahmatan lil ‘alamin, particularly in Indonesia. Its efforts to promote Islam as a mercy to all creation are evident in its initiatives to educate the community regardless of their background and its humanitarian actions that benefit all of humanity.